Children with autism can track others' beliefs in a competitive game. Issue 3 (19th March 2013) - Peterson, Candida C.; Slaughter, Virginia; Peterson, James; Premack, David
Abstract Theory of mind (ToM) development, assessed via 'litmus' false belief tests, is severely delayed in autism, but the standard testing procedure may underestimate these children's genuine understanding. To explore this, we developed a novel test involving competition to win a reward as the motive for tracking other players' beliefs (the 'Dot‐Midge task'). Ninety‐six children, including 23 with autism (mean age: 10.36 years), 50 typically developing 4‐year‐olds (mean age: 4.40) and 23 typically developing 3‐year‐olds (mean age: 3.59) took a standard 'Sally‐Ann' false belief test, the Dot‐Midge task (which was closely matched to the Sally‐Ann task procedure) and a norm‐referenced verbal ability test. Results revealed that, of the children with autism, 74% passed the Dot‐Midge task, yet only 13% passed the standard Sally‐Ann procedure. A similar pattern of performance was observed in the older, but not the younger, typically developing control groups. This finding demonstrates that many children with autism who fail motivationally barren standard false belief tests can spontaneously use ToM to track their social partners' beliefs in the context of a competitive game.